Pemanfaatan Produk Pertanian sebagai Makanan Tambahan dan Bergizi melalui Posyandu Plus Berbasis Agronursing untuk Mengatasi Stunting - Tantut Susanto; Rokhani Rokhani; Rismawan Adi Yunanto; Ira Rahmawati; Nuning Dwi Merina (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The problem of stunting can be immediately overcome by optimizing the local food sources. The purpose of this community service is to optimize the use of agricultural products as nutritious food through Posyandu Plus with an agronursing approach. The approach taken in this service is through participatory action research in Patemon and Bedadung Villages for 3 months. Partners are involved in the establishment, implementation, and evaluation of the Nursing Feeding Center Care. A series of activities were carried out including health education, group process for making additional food, empowerment in the food diversification program, and the implementation of posyandu plus. The measurement of the success of the program is carried out by increasing the knowledge, attitudes, and behavior of mothers in the care of stunting toddlers. In addition, nutritional status (Z Score) is measured. The results showed that there was an increase in knowledge (17.1±2.1 vs 22.6±1.6; p-value <0.001) attitude (34.7±4.7 vs 40.2±3.5; p-value <0.001), and behavior (32.3±3.5 vs 39.3±3.1; p-value <0.001) of mothers. Furthermore, there was an improvement in stunting problems which was initially stunted by 24.1% to 41.4% not stunting (p-value = 0.027). The agronursing-based posyandu PLUS program was able to overcome stunting problems in the community